Políticas públicas de saúde para mulheres e crianças no Rio Grande do Sul durante o Estado Novo (1937-1945) - Wilke, Fábio Roberto (Universidade do Vale do Rio dos Sinos, 2023)
This thesis investigates public health policies for women and children in the State of Rio Grande do Sul during the period of the Estado Novo, primarily between 1937 and 1945. In the second chapter, "Health as Policy: Public Health in 'The New Politics of Brazil,'" political speeches from Getúlio Vargas that characterized women and children based on their social roles as defined by his government are analyzed. It also explores the Constitutions of 1934 and 1937 to understand how women and children were inscribed in both Constitutional texts and how legal norms for healthcare assistance to these groups were shaped by the Brazilian state. Therefore, based on the understanding that the health of women and children has been subsumed under the maternity-childhood paradigm, a historical critique of this emphasis in the formulation of public policies was conducted. In the third chapter, "Health as Science: The Emergence of Public Health (1934-1947)," the Pan American Health Organization and its Sanitary Bulletins are analyzed to map the rise of public health as a subject and how the health of women and children was discussed in the Bulletins circulated throughout the Americas. Simultaneously, the magazine "O Brasil-Médico" (1935-1946) is examined to map this theme at the national level. Finally, two perspectives on public health are discussed through the 1st National Congress of School Health (1941) and the 1st National Health Conference (1941). The fourth chapter, "Rio Grande do Sul and Public Health Policies for Women and Children (1937-1945)," provides an overview of public health in Rio Grande do Sul and analyzes the public policies for women and children implemented in the state through the district system. It also examines Decrees as instruments for the development of public policies, as well as federal assistance to private maternal and childcare institutions. Finally, it focuses on the analysis of the city of Porto Alegre, investigating how public policies for women and children were implemented in the state capital.
Keywords: Políticas públicas; Saúde; Mulheres e crianças; Estado Novo (1937-1945); Public policies; Health; Women; Children; ACCNPQ::Ciências Humanas::História